A return to the classics? The implementation of royal commissions in Australia. Issue 1 (2nd January 2023) - Stark, Alastair; Punter, Helen; Zarrabi, Behnaz
ABSTRACT: This article examines the extent to which twenty-first century, federal-level Royal Commissions in Australia have been implemented. The findings have been produced from a three-year project which has operationalised a two-stage methodology. Stage one tracked 444 Royal Commission recommendations across six cases to determine the proportion that was implemented or 'shelved' by the government. Stage two interviewed key stakeholders with an interest in each Commission to ascertain whether they propelled substantive policy reforms and the reasons which might explain their success or failure in this regard. Both methods led to a conclusion that Australian Royal Commissions have not been extensively implemented in the twenty-first century. This finding is explained by 'classic' political science explanations and more contemporary policy-orientated explanations, which both suggest that inquiries would do well to future-proof their recommendations from hostile public sector environments if they wish them to be more frequently implemented.